Is contact-line mobility a material parameter? - Jonathan M. Ludwicki; Vanessa R. Kern; Joshua McCraney; Joshua B. Bostwick; Susan Daniel; Paul H. Steen (npj Microgravity, 2022)
Abstract Dynamic wetting phenomena are typically described by a constitutive law relating the dynamic contact angle θ to contact-line velocity U C L . The so-called Davis–Hocking model is noteworthy for its simplicity and relates θ to U C L through a contact-line mobility parameter M, which has historically been used as a fitting parameter for the particular solid–liquid–gas system. The recent experimental discovery of Xia & Steen (2018) has led to the first direct measurement of M for inertial-capillary motions. This opens up exciting possibilities for anticipating rapid wetting and dewetting behaviors, as M is believed to be a material parameter that can be measured in one context and successfully applied in another. Here, we investigate the extent to which M is a material parameter through a combined experimental and numerical study of binary sessile drop coalescence. Experiments are performed using water droplets on multiple surfaces with varying wetting properties (static contact angle and hysteresis) and compared with numerical simulations that employ the Davis–Hocking condition with the mobility M a fixed parameter, as measured by the cyclically dynamic contact angle goniometer, i.e. no fitting parameter. Side-view coalescence dynamics and time traces of the projected swept areas are used as metrics to compare experiments with numerical simulation. Our results show that the Davis–Hocking model with measured mobility parameter captures the essential coalescence dynamics and outperforms the widely used Kistler dynamic contact angle model in many cases. These observations provide insights in that the mobility is indeed a material parameter.